2007
DOI: 10.1523/jneurosci.2944-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Attention Does Not Strongly Modulate Neuronal Responses in Early Human Visual Cortex

Abstract: Attention can dramatically enhance behavioral performance based on a visual stimulus, but the degree to which attention modulates activity in early visual cortex is unclear. Whereas single-unit studies of spatial attention in monkeys have repeatedly revealed relatively modest attentional modulations in V1, human functional magnetic resonance imaging studies demonstrate a large attentional enhancement of the blood oxygen level-dependent (BOLD) signal in V1. To explore this discrepancy, we used intracranial elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 29 publications
5
44
0
1
Order By: Relevance
“…The late interval response phases and the initial stimulus unselective response peaks (at about 50 msec) were of opposite polarity in the two animals. It should be noted that previous studies have also reported interindividual differences in visual cortical LFPs in monkeys (Anderson, Mruczek, Kawasaki, & Sheinberg, 2008;Taylor, Mandon, Freiwald, & Kreiter, 2005) and humans (Yoshor, Ghose, Bosking, Sun, & Maunsell, 2007). Possible causes of these interanimal variations in the shape of the LFP include differences in recording location (e.g., layer; Anderson et al, 2008), that is, foveal versus peripheral stimulus presentations or different cortical layer, in situ electrical properties of electrodes and, although less likely, differences in the location of the reference wires.…”
Section: Discussionmentioning
confidence: 91%
“…The late interval response phases and the initial stimulus unselective response peaks (at about 50 msec) were of opposite polarity in the two animals. It should be noted that previous studies have also reported interindividual differences in visual cortical LFPs in monkeys (Anderson, Mruczek, Kawasaki, & Sheinberg, 2008;Taylor, Mandon, Freiwald, & Kreiter, 2005) and humans (Yoshor, Ghose, Bosking, Sun, & Maunsell, 2007). Possible causes of these interanimal variations in the shape of the LFP include differences in recording location (e.g., layer; Anderson et al, 2008), that is, foveal versus peripheral stimulus presentations or different cortical layer, in situ electrical properties of electrodes and, although less likely, differences in the location of the reference wires.…”
Section: Discussionmentioning
confidence: 91%
“…Future investigations of the relative sensitivity of single units vs. LFPs are needed to clarify this issue. However, a long latency of attentional effects in V1 could explain why some studies found little or no significant average enhancement of response with attention in V1, because these studies generally used short stimulus presentations (3,6,37,38). Likewise, a long latency attentional effect in V1 provides an obvious explanation for why some imaging studies find robust effects of attention in V1 (13).…”
Section: Discussionmentioning
confidence: 99%
“…Modulation in firing rates due to attention are known to be weak in early visual areas, increasing in strength over hierarchical levels (Mehta et al, 2000;Maunsell and Cook, 2002). Similarly, subdural LFP recordings in humans have shown that the effects of spatial attention in V1 on the event-related potential are rather small (Yoshor et al, 2007). The comparatively strong effects of temporal expectation and their global nature indicate that the underlying mechanisms differ from those of spatial attention.…”
Section: Discussionmentioning
confidence: 99%